Dissemination of political issues on tiktok social media and its implications on the political attitudes of students of the University of muhammadiyah malang - Sari, Afifah Yulia; Zuriah, Nurul; Wibowo, Arif Prasetyo (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
TikTok, as a short-video-based social media platform, has become an important space for the dissemination of political issues among university students. This study aims to explore the patterns of political issue dissemination through TikTok and its influence on the political attitudes of students at Universitas Muhammadiyah Malang. Using a qualitative phenomenological approach, six informants were selected through purposive sampling and interviewed semi-structurally, with data analyzed using Braun and Clarke"™s thematic analysis method. The findings reveal that the For You Page algorithm reinforces exposure to specific issues, shapes students"™ political agenda, enhances political awareness and engagement, but also generates risks of polarization, confirmation bias, and disinformation. This study concludes that TikTok plays a dual role as a medium of informal political education and, at the same time, a platform vulnerable to algorithmic filter bubble effects